2022
DOI: 10.3390/ijms23179530
|View full text |Cite
|
Sign up to set email alerts
|

Altered Expression of TMEM43 Causes Abnormal Cardiac Structure and Function in Zebrafish

Abstract: Arrhythmogenic cardiomyopathy (ACM) is an inherited heart muscle disease caused by heterozygous missense mutations within the gene encoding for the nuclear envelope protein transmembrane protein 43 (TMEM43). The disease is characterized by myocyte loss and fibro-fatty replacement, leading to life-threatening ventricular arrhythmias and sudden cardiac death. However, the role of TMEM43 in the pathogenesis of ACM remains poorly understood. In this study, we generated cardiomyocyte-restricted transgenic zebrafish… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 87 publications
0
9
0
Order By: Relevance
“…Several rare TMEM43 variants have been sporadically identified in ACM patients [ 53 , 54 , 55 , 58 , 97 ]. To investigate the molecular mechanism underlying TMEM43 mutation-associated ACM, a truncation mutant was generated by using the CRISPR/Cas9-based gene editing technique to shift the reading frame of the zebrafish tmem43 gene [ 94 ]. Interestingly, significantly enlarged ventricular chamber size was observed in the loss-of-function tmem43 mutants in the adult stage, while no obvious cardiac defects or contractile dysfunction were detected during early embryonic stages.…”
Section: Zebrafish Models Of Acm Genesmentioning
confidence: 99%
See 2 more Smart Citations
“…Several rare TMEM43 variants have been sporadically identified in ACM patients [ 53 , 54 , 55 , 58 , 97 ]. To investigate the molecular mechanism underlying TMEM43 mutation-associated ACM, a truncation mutant was generated by using the CRISPR/Cas9-based gene editing technique to shift the reading frame of the zebrafish tmem43 gene [ 94 ]. Interestingly, significantly enlarged ventricular chamber size was observed in the loss-of-function tmem43 mutants in the adult stage, while no obvious cardiac defects or contractile dysfunction were detected during early embryonic stages.…”
Section: Zebrafish Models Of Acm Genesmentioning
confidence: 99%
“…For the TMEM3 gene, in addition to the aforementioned KO study, transgenic overexpression study on two different ACM-associated TMEM43 variants (P111L and S358L) was also reported [ 94 ]. Transgenic overexpression of TMEM43 gene, either wild-type or mutated (P111L), resulted in cardiac defects such as cardiomyocyte hypertrophy and ventricular chamber enlargement during the early developmental stages in zebrafish.…”
Section: Zebrafish Models Of Acm Genesmentioning
confidence: 99%
See 1 more Smart Citation
“… 43 Alterations in cardiac structure and function have also been shown in a transgenic zebrafish model when TMEM43 variants (c.1073C>T, p.S358L; c.332C>T, p.P111L) were expressed. 44 Both variants displayed cardiac morphological defects at juvenile stages and ultrastructural changes within the myocardium, accompanied by dysregulated gene expression profiles in adulthood. 44 These studies emphasize the importance of bedside to bench for further mechanistic elucidation and hopefully translation back to the bedside to improve patient outcomes.…”
Section: Genetic Etiologymentioning
confidence: 99%
“… 44 Both variants displayed cardiac morphological defects at juvenile stages and ultrastructural changes within the myocardium, accompanied by dysregulated gene expression profiles in adulthood. 44 These studies emphasize the importance of bedside to bench for further mechanistic elucidation and hopefully translation back to the bedside to improve patient outcomes.…”
Section: Genetic Etiologymentioning
confidence: 99%